RECOMBINATION OF MINANGKABAU TRADITIONAL ARTS IN ALAM TAKAMBANG JADI BATU BY KOMUNITAS SENI NAN TUMPAH - IKHSAN SATRIA IRIANTO; SAADUDDIN SAADUDDIN; SUSANDRO SUSANDRO; NOLLY MEDYA PUTRA (LPPMPP Institut Seni Indonesia Padangpanjang, 2020)
This study aims to find out how the exploration of Minangkabau traditional art carried out by the Nan Tumpah Art Community (KSNT) in the Alam Takambang Jadi Batu by Mahatma Muhammad. KSNT is an art group from Padangpariaman which has a tendency to utilize Minangkabau traditional art as its artistic material. In efforts to explore the Minangkabau traditional art in the work of Alam Takambang Jadi Batu, the research method used is a qualitative method with an interpretive descriptive approach. Based on the results of the study it can be concluded, KSNT utilizes and processes Minangkabau traditional arts, such as Randai, Indang and Tupai Janjang. The conclusion obtained from this research is that KSNT utilizes traditional art as an effort to revitalize traditional arts for modern aesthetic needs. KSNT calls this traditional art exploration process a